Chemical profile of the Anatolian Sideritis species with bioactivity studies - Sema Çarıkçı; Turgut Kılıç; Ahmet C. Gören; Tuncay Dirmenci; Gülbahar Özge Alim Toraman; Gülaçtı Topçu (Taylor & Francis Group, 2023)
AbstractContext The genus Sideritis L. (Lamiaceae) is represented by 46 species in Turkey with an 79% endemism ratio, 42 of 46 belonging to the section Empodoclia.Objective In this review article, Sideritis species growing in Turkey have been evaluated for phytochemical constituents and biological activities.Methods The data for the isolates, components and extracts of the Anatolian Sideritis species and their bioactivity studies were retrieved from the main databases WoS, Scopus and PubMed from 1975 until 31 December 2022.Results In this review article, terpenoids, flavonoids, phenolics and other secondary metabolites isolated from Turkish Sideritis species were reported. Anatolian Sideritis species, which primarily consist of monoterpenes and sesquiterpenes, were studied in detail. Sideritis plants are represented by 46 species in Turkey, and 25 of them were investigated for their diterpenoids through isolation or LC-MS studies. Most of the diterpenoids of Turkish Sideritis species have ent-kaurene skeleton, among them linearol, siderol, 7-epicandicandiol and sideridiol were found to be the main compounds. Exceptionally, labdane, pimarane and beyerene diterpenoids were only found in a few species. For phenolics and flavonoids, only 12 species were investigated until now, and they were found to be rich in phenylethanoid glycosides and flavonoid glycosides. In terms of activity, most of the species were tested for antioxidant activity, followed by antimicrobial and anti-ulcer/anti-inflammatory activities. Their cytotoxic, enzyme inhibitory, antinociceptive and antistress activities were less frequently studied.Conclusions Sideritis species should be considered promising therapeutic agents in the treatment of upper respiratory tract and ulcer/inflammatory diseases.